The Study of Article’s Distribution of Lancang Kuning On Garuda: Garba Rujukan Digital (Garba Digital Refference) - Triono Dul Hakim; Vita Amelia (Human Sustainability Procedia, 2018)
The study conducted in October 2018 discusses the distribution of articles about Lancang Kuning which can be accessed through the Garuda database. This study was carried out by searching by using the Lancang Kuning keyword through the GARUDA database: Digital Referral Garba. The purpose of this study is to find out how far Lancang Kuning has been raised in the study of lecturers and / or researchers in Indonesia by year, name of journal and the most active writer. Data that has been collected is separated by year, journal where the article is published and based on the author’s name. The results of the study show: 1. The article on Lancang Kuning was most widely published in 2015 reaching 25.60%. 2. Articles about Lancang Kuning published by the Journal published by Lancang Kuning University reached 54.71% compared to journals outside Unilak. The most widely published journal in Unilak is Jurnal Ilmu Budaya from the Faculty of Humanities. 3. The most productive writers are Ermina Sari, Nining Sudiar, Abrar Tanjung and Jumiati